PENDIDIKAN KARAKTER DALAM PERSPEKTIF SUNNAH SEBAGAI UPAYA PENINGKATAN MUTU BINA PRIBADI ISLAMI PADA PESERTA DIDIK DI MTS AL ARIFIN KECAMATAN PANGKALAN BARU PROVINSI BANGKA BELITUNG - Ani Susanti (UNISAN JURNAL, 2024)
Character education is the core of Islamic education, which was originally known as moral education. Moral education has existed since Islam was preached by the Prophet to his companions. Along with the spread of Islam, character education has never been neglected because the Islam preached by the Apostle is Islam in the full sense, namely integrity in faith, righteous deeds and good morals. The aim of character or moral education is to overcome the moral decline that occurs in the current generation. Character problems are problems that must be overcome together with elements of the nation. Because this is a big problem facing the Indonesian people in this era of advanced technology. Progress over time has been accompanied by a decline in the morals of the younger generation who are the hope of the nation. The methodology in this research is qualitative research in the form of field research which is supported by literature study. This research was conducted because moral issues are a problem that must be of common concern. Morals or character can be grown and formed with education. Character education is one solution to this problem. Character education takes concepts from the Qur’an, the Sunnah of the Prophet SAW and government concepts to support the character education strengthening program (PPK) that has been launched by the government. The conclusion in this research is that character education can be integrated into learning at school in all subjects, especially Islamic Religious Education as a subject that plays a major role in instilling religious values in students. Character education is used as an effort to improve the quality of implementation of Islamic Personal Development activities for students at MTS Al-Arifin, Pangkalan Baru Regency, Bangka Belitung Province.